Djelfa 41-43. Un camp d’internement en Algérie : addenda iconographique - Bernard Sicot (Cahiers de Civilisation Espagnole Contemporaine)
Sometimes the stubbornness of researcher is rewarded. Sometimes, a little too late, however. This is what happened with Djelfa 41-43. Un camp d’internement en Algérie (Paris, Riveneuve éditions, 2015), a book that gathers - to trace the history and life of this emblematic place where were deported, with many others and as Max Aub, hundreds of Spaniards - archive documents, texts, often unpublished testimonies and an iconography that I was not able to complete, some images which existence I supposed remained without finding. Now, a few weeks after the release, they appeared. These pages have no other purpose than to let them know.